Evaluating cardiac function with chest computed tomography in acute ischemic stroke: feasibility and correlation with short-term outcome - Bao, Jie; Wang, Chen; Zhang, Yimeng; Su, Zhuangzhi; Du, Xiangying; Lu, Jie (Frontiers in Neurology, 2023)
Background The outcomes of patients with acute ischemic stroke (AIS) are related to cardiac function. Cardiac insufficiency can manifest as hydrostatic changes in the lungs. Computed tomography (CT) of the chest is commonly used for screening pulmonary abnormalities and provides an opportunity to assess cardiac function. Purpose To evaluate the correlation between hydrostatic lung manifestations on chest CT and cardiac function with its potential to predict the short-term outcome of AIS patients. Methods We retrospectively analyzed AIS patients who had undergone chest CT at admission and echocardiogram within 48 h. Morphological and quantitative hydrostatic changes and left ventricular dimensions were assessed using chest CT. Improvement in the National Institutes of Health Stroke Scale (NIHSS) score on the seventh day determined short-term outcomes. Multivariate analysis examined the correspondence between hydrostatic lung manifestations, left ventricular dimension, and left ventricle ejection fraction (LVEF) on echocardiography, and the correlation between hydrostatic changes and short-term outcomes. Results We included 204 patients from January to December 2021. With the progression of hydrostatic changes on chest CT, the LVEF on echocardiography gradually decreased (p < 0.05). Of the 204, 53 patients (26%) with varying degrees of hypostatic lung manifestations had less improvement in the NIHSS score (p < 0.05). The density ratio of the anterior/posterior lung on CT showed a significant negative correlation with improvement in the NIHSS score (r = −5.518, p < 0.05). Additionally, patients with a baseline NIHSS ≥4 with left ventricular enlargement had significantly lower LVEF than that of patients with normal NIHSS scores. Conclusion Hydrostatic lung changes on chest CT can be used as an indicator of cardiac function and as a preliminary reference for short-term outcome in AIS patients.